A Novel Reactivity Descriptor for mn4 Molecular Catalysts for the Oxidation of 2-Mercaptoethanol and of Thioglycolic Acid: The Electrochemical Hardness - Zagal-Moya, J; Zagal-Moya, J; Ponce-Hormazabal, I; Scarpetta-Pizo, L; Scarpetta-Pizo, L (Elsevier Inc., 2025)
This manuscript describes a novel reactivity descriptor for Fe phthalocyanines molecular catalysts confined on the surface of OPG electrodes. The descriptor ΔE°’cat. is the gap in potential between the E°Fe(III)/(II) and E°Fe(II)/(I) redox processes for each FeN4 catalyst. This descriptor, labeled as the electrochemical hardness ΔE°’cat. Was examined using FeN4 macrocyclic complexes for the electrooxidation of 2-mercaptoethanol (2-ME) and thioglycolic acid TGA. Our findings reveal that the reactivity as log log(j/Γ)E, plotted versus E°Fe(III)/(II) or E°Fe(II)/(I) give two linear correlations. The activity log(j/Γ)E in both cases decreases with the redox potential of each FeN4 catalyst. In contrast log(j/Γ)E, or log (TOF)E, increase with ΔE°’cat.. The Fe[sbnd]S binding energy ΔE°’cat. Correlates linearly with ΔE°’cat. so the softer the system the greater the binding energy and the lower the catalytic activity. © 2024